Non-native Brachiaria humidicola with biological nitrification inhibition capacity stimulates in situ grassland N2O emissions - Xie, Lu; Liu, Deyan; Chen, Zengming; Niu, Yuhui; Meng, Lei; Ding, Weixin (Frontiers in Microbiology, 2023)
Brachiaria humidicola, a tropical grass, could release root exudates with biological nitrification inhibition (BNI) capacity and reduce soil nitrous oxide (N2O) emissions from grasslands. However, evidence of the reduction effect in situ in tropical grasslands in China is lacking. To evaluate the potential effects of B. humidicola on soil N2O emissions, a two-year (20152017) field experiment was established in a Latosol and included eight treatments, consisting of two pastures, non-native B. humidicola and a native grass, Eremochloa ophiuroide, with four nitrogen (N) application rates. The annual urea application rates were 0, 150, 300, and 450 kg N ha–1. The average two-year E. ophiuroides biomass with and without N fertilization were 9.07–11.45 and 7.34 t ha–1, respectively, and corresponding values for B. humidicola increased to 31.97–39.07 and 29.54 t ha–1, respectively. The N-use efficiencies under E. ophiuroide and B. humidicola cultivation were 9.3–12.0% and 35.5–39.4%, respectively. Annual N2O emissions in the E. ophiuroides and B. humidicola fields were 1.37 and 2.83 kg N2O-N ha–1, respectively, under no N fertilization, and 1.54–3.46 and 4.30–7.19 kg N2O-N ha–1, respectively, under N fertilization. According to the results, B. humidicola cultivation increased soil N2O emissions, especially under N fertilization. This is because B. humidicola exhibited the more effective stimulation effect on N2O production via denitrification primarily due to increased soil organic carbon and exudates than the inhibition effect on N2O production via autotrophic nitrification. Annual yield-scale N2O emissions in the B. humidicola treatment were 93.02–183.12 mg N2O-N kg–1 biomass, which were significantly lower than those in the E. ophiuroides treatment. Overall, our results suggest that cultivation of the non-native grass, B. humidicola with BNI capacity, increased soil N2O emissions, while decreasing yield-scale N2O emissions, when compared with native grass cultivation.